Pertumbuhan Bibit Kakao (Theobroma Cacao L) pada Media Tanah Ultisol yang diberi Perlakuan Pupuk Kompos Kotoran Sapi - Yuza Defitri; Ida Nursanti; Andry Kurniawan (Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the growth of cocoa seedlings on Ultisol soil treated with cow dung compost. This research was conducted in the piyo garden, Batanghar University, Jambi Campus II. The environmental design used was a completely randomized design (CRD) and the treatment design was cow dung compost which consisted of 4 treatments: K0 = no treatment (control), K1 = 100 gr/polybag of cow dung, K2 = 150 gr/polybag of cow dung, K3 = 200 gr/poly bag of cow dung. Observational data were analyzed using analysis of variance, if there was a significant effect it was followed up with Duncan's Multiple Range Test (DNMRT) at the 5% level. The results showed that the application of cow dung compost at different doses had a significant effect on plant height and stem diameter and had no significant effect on plant dry weight and root dry weight. Cocoa plant height increased by 36.64% and stem diameter by 18.26% with K3 treatment compared to the amount without treatmentKeywords: cow dung compost, Ultisol and cocoa